The Effect of Transfer Pricing, Sales Growth, and Leverage on Tax Avoidance with Company Size as a Moderating Variable - Parahita, Aulia Hanesti; Tjahjono, Mazda Eko Sri (Dinasti Publisher, 2025)
This study uses company size as a moderating variable to examine how transfer pricing, sales growth, and leverage have an effect on tax avoidance. Manufacturing firms that were listed on the Indonesia Stock Exchange (BEI) in 2018 to 2022 make up the study's population. Fifty four firms were decided on as samples for this examine the usage of the purposive sampling approach. the use of SPSSv25 software program, moderated regression analysis (MRA) become used to analyse the statistics. The findings indicate that even as transfer pricing has no discernible impact on tax avoidance, sales growth and leverage have a positive effect. Furthermore, whilst company size can moderate the effect of leverage and sales growth on tax avoidance, it has no affect on the impact of transfer pricing.